THE MATURITY OF KNOWLEDGE MANAGEMENT PRACTICES IN THE MALAYSIAN PUBLIC SECTOR - Kamsuriah Ahmad; Subashini Ganapathy; Zulkefli Mansor, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The main purpose of Knowledge Management (KM) is to improve organizational efficiency by optimizing all available resources or assets. Therefore, organization should provide an environment that is conducive for the KM to be practiced at its best. Although KM has been introduced earlier but its practice in the Malaysian public sector is still in its infancy. This may be due to the lack of support and understanding in practicing KM activities, as a result implementing these activities often fails. Therefore, identifying the level of KM practice of employees is important, and proposing the evaluation factors becomes the main focus of this study. These identified factors can be used to assess the maturity level of KM practices in the organization. The maturity of KM practice refers to the level of acceptance and achievement of KM in the organization. If KM achievement level is not satisfied then improvements need to be made by each entity in the organization until it reaches the highest performance. This entity is referring to a wide spectrum of operations such as people, organizational processes, business initiatives or technology. In identifying the factors, the review from existing literature has been made. Based on people-process-technology framework, this study proposes four factors and sixteen sub-factors in determining the maturity of KM practices in the organization. All these factors have been confirmed by three KM experts and practitioners in the public sector organizations.